O movimento dos saberes na produção da vida na Comunidade Quilombola Campina de Pedra - Guerino, Mariana de Fátima (2013)
In the understanding of multiple human possibilities, we bring to light the movement of production possibilities of life through labor associated in the Community Quilombola Campina de Pedra. We seek information about the historical changes in forms of labor under capitalism and possible lapses proliferation of differentiated cultures of work in its own essence. We hope to stimulate discussions about the work or the associated production and consider the associated knowledge concerning them as processes of human development, education and work where they constitute inseparable. So will try to trace some considerations about these concepts, as well as reflect on its historical roots, from the multiple experiences throughout history interfaces with the knowledge produced in the context of dynamic maintenance of human existence. We will seek to understand the production or the work associated not constitute sealed as concepts, but constantly moving in the interstices of capitalist dynamics where humans are engaging on their essential ability to think and evaluate possibilities, probabilities and alternatives so they can ensure expanded production of life without submission to the oscillations of a mode of production that favors the few and belittles the vast majority of humans. In this context we give prominence to quilombola identity in their relationship with the land and in creating and maintaining solidary forms of life contained in the historical root of the ancestors of those who now live in this unique space called Comunidade Quilombola Campina de Pedra.